2020
DOI: 10.1111/mcn.12966
|View full text |Cite
|
Sign up to set email alerts
|

Cash and voucher assistance and children's nutrition status in Somalia

Abstract: To address ongoing food insecurity and acute malnutrition in Somalia, a broad range of assistance modalities are used, including in‐kind food, food vouchers, and cash transfers. Evidence of the impact of cash and voucher assistance (CVA) on prevention of acute malnutrition is limited in humanitarian and development settings. This study examined the impact of CVA on prevention of child acute malnutrition in 2017/2018 in the context of the Somalia food crisis. Changes in diet and acute malnutrition were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 14 publications
1
31
2
Order By: Relevance
“…When comparing food voucher recipients with mixed transfer recipients, the change over time in both mean MUAC and prevalence of acute malnutrition was similar. 34 Likewise, a UCT programme targeting pregnant and lactating women found no significant difference in preventing acute malnutrition compared with a control group with no cash-related intervention. 33 When 6 monthly cash transfers (US$40 per month) were compared with food vouchers and food transfers in Northern Ecuador, all three arms significantly improved the quality and quantity of consumed food (measured by HDDS, Dietary Diversity Index (DDI), FCS, caloric intake, per capita food consumption).…”
Section: Resultsmentioning
confidence: 97%
“…When comparing food voucher recipients with mixed transfer recipients, the change over time in both mean MUAC and prevalence of acute malnutrition was similar. 34 Likewise, a UCT programme targeting pregnant and lactating women found no significant difference in preventing acute malnutrition compared with a control group with no cash-related intervention. 33 When 6 monthly cash transfers (US$40 per month) were compared with food vouchers and food transfers in Northern Ecuador, all three arms significantly improved the quality and quantity of consumed food (measured by HDDS, Dietary Diversity Index (DDI), FCS, caloric intake, per capita food consumption).…”
Section: Resultsmentioning
confidence: 97%
“…[36,37] Further longitudinal research is needed to provide nuanced understanding of how cash, including delivering modality and dosage, and contextual factors may influence nutrition related outcomes, beyond food insecurity. [38] While we are only able to assess changes in depressive symptoms and perceived household needs and daily stressors over time without a comparison group, data point to a potential relationship between cash assistance and mental health outcomes both during and after the assistance. Qualitatively, some women described cash meaningfully reducing the daily stressors facing women and their families.…”
Section: Discussionmentioning
confidence: 99%
“…Such interventions have helped improve the nutrition outcomes in similar contexts. Studies in multiple countries have shown that cash transfers alone or in combination with other interventions prevented malnutrition and improved outcomes (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%